Nurses’ Experiences in end-of-Life Care in an Intensive Care Unit at Tertiary Healthcare Setting, Lahore - Muhammad Bilal, Farhan Mukhtar, Samina Kousar, Mansoor Ghani, Mehdi Hayat Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: End-of-life care has emerged as an essential component of health care organizations. Now a day, end-of-life care is debated more intensively among patients and their families. Moreover, nurses working in the Intensive Care Unit perform their duties under extreme pressure. A reason for this extreme stress is a shortage of nurses and other healthcare resources. Patients’ and family demands at the terminal stage of life further impact nurses’ experiences of end life care. Thus, the current study was conducted with the aim of following objective. Objective: To explore Nurses’ Experiences in End-of-Life Care in an Intensive Care Unit at Tertiary Healthcare Setting, Lahore Methodology: A qualitative descriptive phenomenological research design was adopted to describe Nurses’ Experiences in End-of-Life Care in an Intensive Care Unit at Tertiary Healthcare Setting, Lahore The target population was registered nurses who have been working in intensive care units for more than one year and are actively involved in the end life care. In depth interviews were conducted with a sample of 10 nurses until saturation of responses. Results: Thematic analysis was carried-out. From the experiences of 10 nurses, 5 themes were extracted i.e. multifactorial influences of end life, financial issues, counseling, and communication, ignored care and administrative challenges for nurses. The results of the study revealed that ELC is influenced by religion and spirituality and nurses experienced problems in managing financial issues, communicating with patients and families. Conclusion: Nurses need to encourage and participate in managing financial resources for patient care and they must also be involved in continuous education programs especially focusing on therapeutic communication and professional counseling. Furthermore, administrative policies must support nurses’ sovereignty in their domain of practice. Keywords: Intensive Care Unit, Nurses’ Experiences, End life care, tertiary health care setting.